Illocutionary Speech Act Strategies in Stand-Up Comedy by Indra Jegel and Russell Peters: A Cross-Cultural Pragmatic Perspective - Putri Kholifatun Nafisah; Eti Setiawati (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
Stand-up comedy is a monologue-based comedy that relies on the use of language as a means of constructing humor and conveying criticism. The use of language can be influenced by cultural backgrounds, which may potentially result in differences in the types and strategies of illocutionary speech acts employed by comedians. This study aims to describe and compare the types and strategies of illocutionary speech acts used by comedians Indra Jegel and Russell Peters from a cross-cultural pragmatic perspective. This research employs a qualitative approach using a case study method. The research data consists of utterances produced by Indra Jegel and Russell Peters containing illocutionary speech acts, obtained from two YouTube channels, namely Stand Up Kompas TV and the Just for Laughs channel. Data collection was conducted through observation and note-taking techniques. The data analysis technique consists of three main stages: data reduction, data presentation, and conclusion drawing/verification. The results of the study indicate that Indra Jegel tends to employ expressive and representative speech acts with varied strategies, while also utilizing nonverbal elements that reflect the characteristics of a high-context culture. Meanwhile, Russell Peters predominantly uses directives and representative speech acts with direct and literal strategies, reflecting the characteristics of a low-context culture. This study demonstrates that differences in the types and strategies of illocutionary speech acts in the stand-up comedy performances of Indra Jegel and Russell Peters are closely related to the cultural communication patterns of their respective countries, as explained through cultural context theory. This research is expected to contribute to the development of cross-cultural pragmatic studies and help society better understand intercultural communication patterns.